PENGARUH FAKTOR PEMILIHAN LOKASI TERHADAP EFEKTIVITAS PASAR PANGGUNGREJO - Siswantika, Yohanita Pudyas; Nurhadi, Kuswanto; Andini, Isti (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2015)
Accordingly increasing of street vendors especially in Surakarta, City Goverment of Surakarta have been taking policy to relocated street vendors to market. Panggungrejo market serve as a place to relocated street vendors that selling on Ki Hajar Dewantara street. It is taken for maintain the beauty and neatness of city, furthermore to maintaining the continuity of street vendors selling. There are many thing that be supposed in relocated street vendors to market, one of which is a factor of location choice because it will affect the market crowd. Altought the location of Panggungrejo market close to the initial location of street vendors and theyâ€™re selling almost the same kind of wares, but the market conditions are very quiet and merchants complained of a decrease in turnover, so they chose to sell elsewhere. The question in this research is how the site selection factors influence the effectiveness Panggungrejo Market. The method in this research is deductive-quantitative. The analysis used in this study consisted of descriptive analysis is descriptive narrative and descriptive eksplanatif, as well as multiple regression statistical analysis. Results from this research that despite support for the crowded market place, but the condition of Panggungrejo market is still not effective. There are only three of the nine site selection factors that influence the inefficiencies of Panggungrejo market that are competitors, visibility and market facilities. Therefore, ineffectiveness of Panggungrejo market may also be influenced by other factors.Â Keywords: Market, Relocation, Effectiveness, Site Selection Factors